Source Base for Investigation of the Development of Vocational-Technical Education in Ukraine in 40–50-s of the 20-th Century - Ivchenko, Tetyana (Pedagogical Discourse, 2013)
Development of the system of vocational training in 40-50-s of the ХХ century, preconditions of manpower reserves system creation are found out, the analysis of qualitative changes and perfection of industrial practice, educational, methodical work during pre-war time, in days of war, in renewal of a national economy and growth of rates of manufacture in the Great Patriotic War is given. Professional – technical education in Ukraine in 40–50-s of the 20 century is described and the suggestions for its implementation during the current system of workers’ training reforms the in the state are represented. Activity and role of special secondary schools in 1940 this considered, efficiency and necessity of the labour on enterprises is proved.